2011
DOI: 10.4028/www.scientific.net/amm.94-96.1261
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Axial-Compression Reinforced Concrete Column Strengthened by Circular Steel Tube

Abstract: In the case of small increase of cross-section, concrete column strengthened by circular steel tube can increase the bearing capacity greatly as well as ductility. This has resulted in engineering welcome. This paper studied the common work performance of reinforced concrete column strengthened by circular steel tube in three different conditions test of axial compression. The results show that outsourcing steel and core column can be achieved interaction. By strengthening, it can improve the load capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In order to fully verify the accuracy and effectiveness of the proposed model, the FEM modeling method introduced in Section 4.2 is used to conduct modeling analysis on the samples in similar literature [41,42,45,68,69], and the analysis results are compared with the test data. e following is a brief introduction to the experimental overview of literature [41,42,45,68,69]:…”
Section: Validation Of Fem Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to fully verify the accuracy and effectiveness of the proposed model, the FEM modeling method introduced in Section 4.2 is used to conduct modeling analysis on the samples in similar literature [41,42,45,68,69], and the analysis results are compared with the test data. e following is a brief introduction to the experimental overview of literature [41,42,45,68,69]:…”
Section: Validation Of Fem Modelmentioning
confidence: 99%
“…e research showed that the shear and flexural capacity of the strengthened column could be greatly improved by the externally wrapped steel strengthening method. Wang [45] made four RC columns strengthened by circular steel tubes, of which two were strengthened by steel pipes without initial load, and the other two were strengthened by steel pipes with initial axial load of 500 kN and 1000 kN, respectively. e gaps between steel pipes and RC column were filled with cement mortar material of the same grade and high-strength nonshrinkage grouting material, respectively.…”
Section: Validation Of Fem Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…e results showed that the CFST jacketing method was much more effective in enhancing the loadbearing capacity and ductility. Wang [25] and He et al [26] studied the effects of preloading on the compressive strength of CFST jacketed columns. e results showed that the preloading level had little effect on the load-bearing capacity of specimens.…”
Section: Introductionmentioning
confidence: 99%